2002
DOI: 10.1113/jphysiol.2002.016600
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of caged cyclic AMP in the ciliary cytoplasm of the newt olfactory receptor cell

Abstract: The effects of cyclic nucleotide monophosphate (cNMP) in the ciliary cytoplasm of the olfactory receptor cell were examined by using photolysis of caged cNMP loaded from the whole‐cell patch clamp pipette. Illumination of the cilia induced an inward current at −50 mV. The current amplitude was voltage dependent and the polarity was reversed at +10 mV. The amplitude of the light‐induced current was dependent on both light intensity and duration. The intensity‐response relation was fitted well by the Hill equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 37 publications
4
71
1
Order By: Relevance
“…Similarly, cytoplasmic photolysis of caged cAMP induced inward current responses with similar profiles as the odorant-induced current ( Fig. 1 D, E) (n H ϭ 5.1 Ϯ 1.9; n ϭ 21) (Takeuchi and Kurahashi, 2002). This indicates that the nonlinear amplification is established at the downstream point from the cAMP production and has been interpreted to be attributed to the involvements of two different transduction channels, namely, CNG channels and Ca 2ϩ -activated Cl Ϫ channels ( Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, cytoplasmic photolysis of caged cAMP induced inward current responses with similar profiles as the odorant-induced current ( Fig. 1 D, E) (n H ϭ 5.1 Ϯ 1.9; n ϭ 21) (Takeuchi and Kurahashi, 2002). This indicates that the nonlinear amplification is established at the downstream point from the cAMP production and has been interpreted to be attributed to the involvements of two different transduction channels, namely, CNG channels and Ca 2ϩ -activated Cl Ϫ channels ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Single receptor cells were enzymatically (0.1% collagenase) dissociated from the olfactory epithelium of the newt Cynops pyrrhogaster, as described previously (Kurahashi, 1989;Takeuchi and Kurahashi, 2002). Cells were bathed in the normal Ringer's solution containing the following (in mM): 110 NaCl, 3.7 KCl, 3 CaCl 2 , 1 MgCl 2 , 10 HEPES, 15 glucose, and 1 pyrvate, pH adjusted to 7.4 with NaOH, before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other molecular mechanisms, including phosphorylation of olfactory receptors (35,36) and adenylyl cyclase (37)(38)(39), have been proposed to play a role in odor adaptation. By using combined molecular, cellular, and behavioral analyses of gene-targeted mice, we can now begin to evaluate the relative contribution of each of these mechanisms to odor perception.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, several aspects of the response to a subsequent stimulus are altered, including a decrease in the slope of the rising phase, as well as an increase in the speed of decay, of the stimulus-induced inward current (7,13). Experiments (15) have demonstrated that the molecular mechanisms responsible for desensitization are likely to act upstream of cAMP production; inhibition of adenylyl cyclase activity by CaMK is a possible mechanism (13). Longer-lasting adaptation effects with recovery time constants of minutes also have been reported (7).…”
mentioning
confidence: 99%